Changes in Rocky Intertidal Community Structure During a Marine Heatwave in the Northern Gulf of Alaska - Weitzman, Benjamin; Konar, Brenda; Iken, Katrin; Coletti, Heather; Monson, Daniel; Suryan, Robert; Dean, Thomas; Hondolero, Dominic; Lindeberg, Mandy (Frontiers in Marine Science, 2021)
Marine heatwaves are global phenomena that can have major impacts on the structure and function of coastal ecosystems. In May 2014, the Pacific Marine Heatwave (PMH), or “Blob”, was evident in intertidal waters of the northern Gulf of Alaska and persisted for multiple years. While offshore ecosystems were likely to respond to the effects of warmer waters, it remained unclear if and how rocky shorelines would respond to the PHM. Intertidal resources are important to coastal human communities for food and recreation, while simultaneously supporting a growing coastal tourism industry. Given that current climate change projections suggest increased frequency and duration of marine heatwaves, monitoring intertidal habitats can inform resource managers and users about future variation in intertidal resources and identify potential mechanisms driving change. We examined sessile community structure at 21 rocky intertidal sites, part of the Gulf Watch Alaska long-term monitoring program, across four regions spanning 1200 km of coastline: Western Prince William Sound, Kenai Fjords National Park, Kachemak Bay, and Katmai National Park and Preserve. Sites were monitored annually from 2012 to 2019 at mid and low tidal strata. Before-PMH community structure was clearly different among regions and between strata and appeared to vary independently within each region. During/after-PMH, similarities in community structure increased across regions due to a Gulf-wide decline in macroalgal cover, driven mostly by a decline in the rockweed, Fucus distichus, and fleshy red algae in 2015, followed by an increase in barnacle cover in 2016, and an increase in mussel cover in 2017 that expanded into the low tidal stratum. While local variation at the site level plays a large role in shaping patterns of community structure, the region-wide shift from a macroalgal dominated rocky intertidal to a filter-feeder dominated state concurrent with the changing environmental conditions associated with a heatwave event suggests the PMH had Gulf-wide impacts to the structure of rocky intertidal communities, which continued after the PMH had dissipated in 2017. Strong, large-scale oceanographic events, like the PMH, may override local drivers to similarly influence patterns of community structure despite regional differences.